Relevansi Kurikulum 2013 Dalam Membentuk Karakter Religius Siswa (Studi Hambatan dan Tantangan Guru PAI di Era Revolusi Industri 4.0) - Imron Rosyadi; Ainur Cahyati (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2022)
The expansion of digital and virtual systems, which is a hallmark of the fourth industrial revolution, has contributed to the loss of authority over the educational landscape. As a result, in this time and place, the religious character must be developed via education. Researchers are interested in undertaking a study named